Selected European Groups and White Racialization: An Illustrative Study: Одбрани европски групи и белата расизација: Илустративна студија - Levine-Rasky, Cynthia (Identities: Journal for Politics, Gender and Culture, 2006)
Author(s): Cynthia Levine-Rasky | Синтија Левин-Раски Title (English): Selected European Groups and White Racialization: An Illustrative Study Title (Macedonian): Одбрани европски групи и белата расизација: Илустративна студија Translated by (English to Macedonian): no record Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 5, No. 2 (Summer 2006) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 143-157 Page Count: 14 Citation (English): Cynthia Levine-Rasky, “Selected European Groups and White Racialization: An Illustrative Study,” Identities: Journal for Politics, Gender and Culture, Vol. 5, No. 2 (Summer 2006): 143-157. Citation (Macedonian): Синтија Левин-Раски, „Одбрани европски групи и белата расизација: Илустративна студија“, Идентитети: списание за политика, род и култура, т. 5, бр. 2 (лето 2006): 143-157.